Práctica de enseñanza de Lengua y Literatura en educación general básica, análisis de caso en tercer año en la unidad educativa San Juan de Ilumán del cantón Otavalo - Díaz Cajas, María Lucila (2016)
This work is focused in qualitative measurement of the teaching practice in the education system. It is meant to know and show the different approaches done for teachers to keep up to date in pedagogical matters in education centers for Language and Literature. The information gathered evidences the experiences how the process occur, how it can help in orderly manners put in place the teaching and learning methods and how this processes are applied, how evaluation forms are put in place, forms of planning the best learning –teaching methods to share in class and the relationship teacher-students. In this theorical framework it take in consideration, the definition of what means teaching practices from well know author in this subject as well the definition provided by the Ministry of Education of the Republic of Ecuador. In this work, it also analyze the changes introduced into the curriculum by the ministry of education. The techniques used for collecting data for this work were: interviews of people involved in the education system and the observation and analysis of documents related to education available, the data collected in to field work, which introduced to the education world to experience the challenges that is facing, understand it better, and the field work will introduce in real time.